Utilization of Partially Purified Milk Clotting Protease from Ginger Rhizome in the Manufacturing of Fresh Cheese - Maskey, Bunty; Pandey, Trilochan; Shrestha, Shiva Kumar; Shrestha, Nabindra Kumar; Shrestha, Megha; Karki, Dhan Bahadur (Himalayan Journal of Science and Technology, 2023)
This study was carried out to utilize the partially purified ginger rhizome protease in fresh cheesemaking. The crude ginger rhizome extract was partially purified by employing 30-80% (NH4)2SO4 saturations (w/v). The maximum milk clotting activity was achieved at 50% saturation, exhibiting the purification fold of 1.64 and activity recovery of 85.76%. The milk pH and temperature for optimum time of coagulation and milk clotting activity were optimized by using response surface methodology (RSM). A numerical optimization study revealed that the optimum milk pH and temperature for producing cheese were 6.5 and 50 C respectively. The cheese produced by ginger protease had significantly (p<0.05) higher moisture, ash and yield, but lower fat content than the rennet cheese. No significant difference (p>0.05) was found in the calcium and protein content of both cheeses. The prepared cheese using ginger protease had significantly (p<0.05) higher spreadability, but lower aftertaste than the rennet cheese. However, non-significant difference (p>0.05) was observed in the flavor and overall acceptance between the two cheeses. Hence, this study demonstrated that the ginger rhizome protease has the potential to be utilized as an effective milk coagulating enzyme in the manufacturing of fresh cheese.